Kinematic and Inertial Interaction of Single and Group Piles in Slope by Displacement Phase Relation. Issue 7 (19th May 2022) - Tran, Nghiem Xuan; Bong, Taeho; Kim, Sung-Ryul
ABSTRACT: This study evaluated the phase relationship among the input motion, ground response, and pile response, which is a key consideration in the analysis of the kinematic–inertial interaction for piles. Dynamic centrifuge tests were conducted on single and group piles embedded in slopes of dry sands. Test results showed that the single pile moved in the opposite phase with the ground movement, whereas the group piles moved nearly in phase. The phase relationship was significantly affected by rocking motion. Therefore, the kinematic force acted as a resistance to the single pile and an additional load to the pile group.